The Seven Deadly Sins : Sayings of the Fathers of the Church - Clarke, Kevin M. (Book collections on Project MUSE., 2018)
"Read this not just for intellectual enjoyment but to discover a centuries-old, proven path for conquering your worst sins" (Brandon Vogt, author of Why I Am Catholic). Gluttony. Lust. Greed. Anger. Sloth. Envy. Pride. The capital vices are the gateway drugs to countless sins. But where did this tradition come from' Unsurprisingly, it can be traced back to the teachings of the Church Fathers, whose words'included in this book'answer such questions as: So how do the capital sins spawn other vices in the soul' How does one cultivate the virtues that heal the soul from those vices' How are gluttony and lust related' What role does almsgiving have in soothing the passion of anger' As the path of the book descends through the vices, the words of the Fathers will assist readers in being more realistic about the attacks upon the soul. Edifying and medicinal, each chapter begins with vice and ends with virtue, so one's path through the chapters represents a sort of ascent out of sin and on to the road to righteousness. The text gives special attention to the thoughts of Augustine of Hippo, Evagrius of Pontus, John Cassian, Gregory the Great, and Maximus the Confessor. "An illuminating survey of the Church Fathers' wisdom on the capital vices that have burdened us since time immemorial." 'Curtis A. Martin, Founder and CEO of FOCUS "A wonderfully helpful compendium of insights and advice from the Church Fathers ... You will be astonished at how relevant and applicable is this ancient wisdom to the life of the modern-day Christian. Highly recommended." 'James Martin, SJ, author of Jesus: A Pilgrimage.